Weight gain and antipsychotics: a drug safety review. (January 2015) - Musil, Richard; Obermeier, Michael; Russ, Paul; Hamerle, Michael
<x xml:space="preserve">Abstract</x> Introduction: Second-generation antipsychotics (SGAs) are widely used in several psychiatric disease entities and exert to a different extent a risk for antipsychotic-induced weight gain (AIWG). As AIWG is associated with an increase in metabolic syndrome or cardiovascular events, knowledge of these risks is crucial for further monitoring and the initiation of counteractive measures. Areas covered: We searched PubMed and Web of Sciences for randomized-controlled trials and naturalistic observational studies published between 2010 and 2014 with sample sizes exceeding 100, including all marketed SGAs apart from zotepine, and providing data on weight increase. We also summarized relevant systematic reviews and meta-analyses of head-to-head comparisons. Expert opinion: Recently published data still support the hierarchical ranking of SGAs already proposed in previous reviews ranking clozapine and olanzapine as having the highest risk, followed by amisulpride, asenapine, iloperidone, paliperidone, quetiapine, risperidone and sertindole in the middle, and aripiprazole, lurasidone and ziprasidone with the lowest risk. Number needed to harm varied considerably in our meta-analysis. Younger patients and patients with a lower baseline body mass index are most vulnerable. The greatest amount of weight gain occurs within the first weeks of treatment. AIWG occurs in all diagnostic groups and is also common in treatment with first-generation antipsychotics; therefore, awareness of this adverse event is essential for anyone prescribing antipsychotics.